Предмет: Математика,
автор: danilf999
Упростить выражение сtg(3п/2+t)*tg(п/2)+cos(п+t)*sin(п/2+t).
Ответы
Автор ответа:
1
По формулам приведения
cos(3п/2+t)=sint
tg(п/2–t)=ctgt
sin(п/2–t)=cost
ctg(3п/2–t)=tgt
ctg(п/2–t)=tgt
Тогда
cos(3п/2+t)tg(п/2–t)–sin(п/2–t)+ctg(3п/2–t)–ctg(п/2–t) =sint·ctgt–cost+tgt–tgt=sint·(cost/sint)–cost=cost–cost=0
Похожие вопросы
Предмет: Биология,
автор: Ansaskov3
Предмет: Музыка,
автор: nuralievanila
Предмет: Английский язык,
автор: gp66pg
Предмет: Алгебра,
автор: Лолло1